El dibujo como primera escritura del niño - Vargas León, Mª del Rosario (2004)
Article that addresses a little explored aspect in the teaching and learning of reading and writing, that is, graphic symbols or drawings made by children. Several national and international investigations have shown that since drawings are part of a child's genesis, they constitute a crucial aspect in his first construction of reading and writing skills. A child can turn drawings into a very effective system of communication. The creating process that constantly makes him face cognitive conflicts that require him to invent and reinvent progressively more communicative ways of expression will prepare him to better understand the conventional alphabet system imposed by his socio-cultural environment. The study was carried out in two Costa Rican schools as part of the outreach project Implementing a constructivist didactics for the beginning reading and writing processes of the Basic Education Division, CIDE, Universidad Nacional. The study has shown that by taking into account the child's genesis for knowledge construction, and by respecting and promoting his symbolic communication, the learning and writing processes become more meaningful to the child.